IMPLEMENTASI PROGRAM INISIASI MENYUSU DINI DAN ASI EKSKLUSIF - E.21108046, Komariyati (FISIP Universitas Tanjungpura, 2013)
TheÂ problem in this study is the lack of awareness of the public to know the Early Initiation of Breastfeeding (IMD) and exclusive breast milk so that had an impact on the conditions of low achievement IMD and exclusive breastfeeding. The low achievement was due to, among others, by the people who deliver at BPS (Midwife Private Practice), the low cakupun continuation program likely caused by several factors such as natural conditions less friendly, and the involvement of health infrastructure is also not very good at the health center in the village . The results showed that the level of knowledge of midwives in the IMD program implementation and exclusive breastfeeding is sufficient. Cause of the lack of success of the IMD and exclusive breastfeeding in the health center in the village is the low level of public education, poverty and socio-economic conditions of the people in the health center in the village of uneven height and besides that the gap between social groups. In addressing the phenomenon that is the author suggested for health personnel especially midwives who served in the delivery room to support early breastfeeding initiation in every mother with spontaneous labor and the baby are in good health.Â Keywords: Initiation, Early Breastfeeding, Exclusive ASI